The Conversational Web - Heck, Larry (Keynote Presentation, IEEE Workshop on Spoken Language Technology, 2012)
There is currently significant interest in the speech, language, and human computer interaction (HCI) scientific communities in creating a conversational interface to the web. Through the combination of natural language (spoken and written) with gesture, touch, and gaze, this natural user interface (NUI) could help you complete online tasks, find what you want, and answer any question as naturally as having a conversation - anytime, anywhere. This talk explores the emergence of this Conversational Web and the fundamental trends in the industry that are providing significant opportunities, and in some cases challenges, for spoken language technologists. The first trend that the talk will cover is the availability of massive data from the Web. A Web of Intents has emerged from the feedback loop of click streams in Web search engines and browsers, capturing many hundreds of millions of queries, page views, and clicks from billions of users every day. This Web of Intents has begun to radically increase the predictive power of statistical learning algorithms underlying modern conversational systems. Second, the talk will discuss the emergence of the Web of Structured Knowledge. With the broadly adopted structuring of web sites through well-formed APIs, the Programmable Web has already enabled the emergence of mobile virtual personal assistants. And with the commitment to adopt standard semantic ontologies, the large search engine companies (Microsoft, Google) are finally making the structured "Semantic Web" a reality. Third, the "Applification" of the Web, which is decentralizing the web into highly structured but fragmented, specialized functional islands. This talk will explore all three trends, and propose some particular approaches to leveraging the first two and turning the third into an asset for the Conversational Web.